Shape reconstruction of specular surface using normal vectors - Yusuf, K.; Edi, P.; Radzi, A.; Ghani, A. (2009)
In the 3-D shape of specular surface measurement, reconstruction of the shape is needed. This paper describes a method of shape reconstruction of specular surface using normal vectors. The normal vectors of the surface are extracted by five degrees of freedom camera system. A normal vector is said to be found when the alignment between the camera axis and the surface normal vector is achieved. These normal vectors then are used as the data for a cubic polynomial function to reconstruct the shape of the surface. The result shows that the methodology improves the 3-D shape of object measurement with good accuracy.